Integration in finite terms with dilogarithmic integrals, logarithmic integrals and error functions. (September 2019) - Kaur, Yashpreet; Srinivasan, Varadharaj R.
Abstract: We extend the theorem of Liouville on integration in finite terms to include dilogarithmic integrals, logarithmic integrals and error functions along with transcendental elementary functions. We also generalise a result of Baddoura on integration in finite terms with dilogarithmic integrals.